A Computer Oriented Method for Solving Transportation Problem (Dhaka University Journal of Science, 2015)
In this paper, an algorithm and its computer oriented program have been developed for solving transportation programming (TP) reducing it into a linear program (LP). After formulating it into linear programming problems the number of variables becomes large. It then, becomes more difficult and time-consuming if it is done manually with simplex method. By using the computer program the solution can be found in a shorter time. It will be shown that a TP with a large number of variables can be solved in few seconds by using this method. A number of numerical examples are presented to demonstrate the method developed in this research. DOI: http://dx.doi.org/10.3329/dujs.v63i1.21758 Dhaka Univ. J. Sci. 63(1): 1-7, 2015 (January)